Tourism and the Less Developed Countries - Harris David (John Wiley & Sons, Ltd, 1995)
A unique analysis of the costs and benefits of tourism in a range of large and small nations. Preface, International Tourism and the Less Developed Countries: The Background, Tourism to Less Developed Countries: The Social Consequences, Political Instability and Tourism in the Third World, The Structure of International Tourism and Tourism Development, Sex Tourism in South-East Asia, Japan and South-East Asia: The International Division of Labor and Leisure, Tourism in Latin America: Perspectives from Mexico and Costa Rica, Tourism Development in Cuba, The Politics of Tour Guiding: Israeli and Palestinian Guides in Israel and Occupied Territories, Life in the Informal Sector: Street Guides in Kandy and Sri Lanka, Tradition and Modernity and Tourism in Swaziland, Bibliography, Index.